2003
DOI: 10.1007/s00404-002-0447-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metformin treatment to ovarian response in cases with PCOS

Abstract: Metformin therapy has led to a higher pregnancy outcome, as well as to a decrease in hyperstimulation risk, cycle cancellations, and multiple pregnancy rates with a lower gonadotropin dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
2
24
1
1
Order By: Relevance
“…Administration of metformin was shown to improve ovarian response to exogenous gonadotropin in women with CC-resistant PCOS (6,8), the dosage of gonadotropins administrated was reduced, as well as a higher pregnancy outcome achieved, by the administration of metformin (11). Studies have elucidated the effect of metformin treatment before IVF in patients with PCOS, which show more mature oocytes collected and higher clinical pregnancy rates obtained than the control group (16,18).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Administration of metformin was shown to improve ovarian response to exogenous gonadotropin in women with CC-resistant PCOS (6,8), the dosage of gonadotropins administrated was reduced, as well as a higher pregnancy outcome achieved, by the administration of metformin (11). Studies have elucidated the effect of metformin treatment before IVF in patients with PCOS, which show more mature oocytes collected and higher clinical pregnancy rates obtained than the control group (16,18).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, metformin administration has been shown to improve ovarian response to exogenous gonadotropin in women with CC-resistant PCOS (6,8). It also has been reported that the dosage of gonadotropins administrated was reduced and a higher pregnancy outcome was achieved by the administration of metformin (11).…”
mentioning
confidence: 97%
“…A total of 28 RCTs potentially resulted for inclusion in the meta-analysis (22,, but of these 11 studies were excluded. In particular, the abortion rate was not evaluated in two studies (35,50), data on the abortion rate were not available from papers and could not be obtained from the investigators after E-mail contact for five studies (30,37,44,53,54), and it was not possible to contact the corresponding investigators for four studies (31,33,47,49). Thus, a total of 17 RCTs (22, 32, 34, 36, 38-43, 45, 46, 48, 51, 52, 55, 56) were included in the final analysis.…”
Section: Resultsmentioning
confidence: 94%
“…This later conclusion was based on three studies with small sample sizes and not necessary designed to establish the risk of multiple births. [47][48][49] . A potential effect of the metformin, used to increase the ovarian response to ovarian stimulators through the reduction of insulin levels in PCOS subfertile women, on the risk of multiple births,noted in this study, merits investigation.…”
Section: Commentmentioning
confidence: 98%